The revisit intentions of local mountaineers to Mount Guiting-Guiting in Sibuyan Island, Romblon: A demographic and behavioral profile - de Torres, Turner Evon; Ulayao, Geronio G. (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
This quantitative study investigates the multifaceted factors influencing local mountaineers’ decisions to return to Mount Guiting-Guiting. Recognizing a notable gap in understanding domestic mountain tourism motivations, particularly within the Philippine context, this research specifically profiles mountaineers based on their key demographic characteristics. It delves into crucial behavioral aspects, encompassing their past climbing experiences, perceived risks associated with the ascent, and overall tourist satisfaction and experience. Employing a descriptive quantitative approach, data was systematically collected from 37 local Filipino mountaineers who have successfully ascended Mount Guiting-Guiting within the last five years. The study examines how perceived risks, tourist satisfaction, and overall tourist experience, as critical behavioral factors, correlate with and potentially influence revisit intentions. Furthermore, a significant analytical component involves determining whether statistically significant differences in revisit intention exist when mountaineers are categorized and grouped according to their socio-demographic profiles. Preliminary findings indicate a strong overall revisit intention among the participants, a sentiment largely driven by the mountain’s breathtaking natural beauty and the profound sense of accomplishment derived from conquering its challenging terrain while demographic factors showed varying influences on specific aspects of satisfaction and perceived risk. This research provides valuable, evidence-based data crucial for developing targeted tourism strategies and implementing sustainable management practices for Mount Guiting-Guiting, thereby aligning product development with the nuanced demands and expectations of this unique and adventurous market segment.